Dampak Transfer: Teknologi, Manajemen Dan Pemasaran Terhadap Produktivitas Dan Biaya Produksi Produk Palm Sugar (Studi Kasus Koperasi Ar-Ridho Nagari Simpang Tonang Kecamatan Duo Koto, Kabupaten Pasaman, Provinsi Sumatera Barat) - Yanuar (Jurnal Ekonomi, 2014)
Limited funds, education and skill levels make the productivity and quality of SME products in general difficult to complete in the free market. Help management, production technology, and marketing from University can improve the quality, productivity, and product marketing SMEs (cooperative). This sutdy compared the productivity and efficiency of palm sugar products Cooperative Ar-Ridho before after management assitance, technology, production and marketing by Tarumanagara University of Jakarta. The empirical findings of this study are increased productivity and improved efficiency of palm sugar products after the transfer technologically, management, and marketing